Acute pulmonary embolism: mortality prediction by the 2014 European Society of Cardiology risk stratification model. Issue 3 (12th May 2016) - Becattini, Cecilia; Agnelli, Giancarlo; Lankeit, Mareike; Masotti, Luca; Pruszczyk, Piotr; Casazza, Franco; Vanni, Simone; Nitti, Cinzia; Kamphuisen, Pieter; Vedovati, Maria Cristina; De Natale, Maria Grazia; Konstantinides, Stavros
The European Society of Cardiology (ESC) has proposed an updated risk stratification model for death in patients with acute pulmonary embolism based on clinical scores (Pulmonary Embolism Severity Index (PESI) or simplified PESI (sPESI)), right ventricle dysfunction (RVD) and elevated serum troponin (2014 ESC model). We assessed the ability of the 2014 ESC model to predict 30-day death after acute pulmonary embolism. Consecutive patients with symptomatic, confirmed pulmonary embolism included in prospective cohorts were merged in a collaborative database. Patients' risk was classified as high (shock or hypotension), intermediate-high (RVD and elevated troponin), intermediate-low (RVD or increased troponin or none) and low (sPESI 0). Study outcomes were death and pulmonary embolism-related death at 30 days. Among 906 patients (mean±sd age 68±16, 489 females), death and pulmonary embolism-related death occurred in 7.2% and 4.1%, respectively. Death rate was 22% in "high-risk" (95% CI 14.0–29.8), 7.7% in "intermediate-high-risk" (95% CI 4.5–10.9) and 6.0% in "intermediate-low-risk" patients (95% CI 3.4–8.6). One of the 196 "low-risk" patients died (0.5%, 95% CI 0–1.0; negative predictive value 99.5%). By using the 2014 ESC model, RVD or troponin tests would be avoided in about 20% of patients (sPESI 0), preserving a high negative predictive value. Risk stratification in patients at intermediate risk requires further improvement. 2014 ESC model in PE accurately identifies low-risk patients; further improvement for intermediate risk is needed http://ow.ly/10b3Qg